2022
DOI: 10.5114/pm.2022.124016
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal hysterectomy reviewed: a stable or aperture for stump cervical malignancy. A referral hospital experience

Abstract: Introduction To review the malignant potential of the stump after subtotal abdominal hysterectomy. Material and methods: Thirty-three patients with stump malignancy were diagnosed and treated between January 2018 and January 2022. All patients primarily underwent subtotal hysterectomy (STH) outside our hospital due to different indications, most of which seemed non-convincing. Upon presentation, they were evaluated properly and offered the best management plan. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Vaccinations against cervical cancer must be kept in mind, and they are an important target to address because 600 women (91.6%) had no idea about the vaccine or its purpose, and even though 35 women (5.3%) were aware of this vaccine, they were not happy to be vaccinated; and only 20 women (3.1%) had taken the vaccine before [22][23][24]. Early diagnosis of cancerous diseases gives a recovery opportunity for the patient, especially by employing therapeutic skills, especially the surgical skills that come to the fore in the surgical steps [25].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations against cervical cancer must be kept in mind, and they are an important target to address because 600 women (91.6%) had no idea about the vaccine or its purpose, and even though 35 women (5.3%) were aware of this vaccine, they were not happy to be vaccinated; and only 20 women (3.1%) had taken the vaccine before [22][23][24]. Early diagnosis of cancerous diseases gives a recovery opportunity for the patient, especially by employing therapeutic skills, especially the surgical skills that come to the fore in the surgical steps [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent publications have contradicted these assertions and revealed that, compared with total abdominal hysterectomy, subtotal hysterectomy did not improve outcomes in terms of urinary or sexual function. Not surprisingly, women who underwent subtotal hysterectomy were more likely to experience postoperative vaginal bleeding from the cervical stump until one year after surgery compared with women who underwent total abdominal hysterectomy [25][26][27]. The potential development of carcinoma on the cervical stump is a further cause of concern.…”
Section: Introductionmentioning
confidence: 99%
“…The potential development of carcinoma on the cervical stump is a further cause of concern. The presence of cancer can be determined with relative accuracy only during the procedure [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation